ANGPTL4 in Metabolic and Cardiovascular Disease. Issue 8 (August 2019) - Aryal, Binod; Price, Nathan L.; Suarez, Yajaira; Fernández-Hernando, Carlos
Abstract : Alterations in circulating lipids and ectopic lipid deposition impact on the risk of developing cardiovascular and metabolic diseases. Lipoprotein lipase (LPL) hydrolyzes fatty acids (FAs) from triglyceride (TAG)-rich lipoproteins including very low density lipoproteins (VLDLs) and chylomicrons, and regulates their distribution to peripheral tissues. Angiopoietin-like 4 (ANGPTL4) mediates the inhibition of LPL activity under different circumstances. Accumulating evidence associates ANGPTL4 directly with the risk of atherosclerosis and type 2 diabetes (T2D). This review focuses on recent findings on the role of ANGPTL4 in metabolic and cardiovascular diseases. We highlight human and murine studies that explore ANGPTL4 functions in different tissues and how these effect disease development through possible autocrine and paracrine forms of regulation. Highlights: ANGPTL4 controls lipoprotein catabolism and energy distribution across different tissues by inhibiting LPL. Excessive lipid storage in adipose tissues and ectopic lipid accumulation in muscle and liver predispose to T2D. Accelerated catabolism of TAG-rich lipoproteins (VLDL and chylomicrons) is associated with decreased risk of coronary artery disease. Recent GWAS findings have shown that genetic variants in the ANGPTL4 locus are associated with protection against T2D and coronary artery disease. Although ANGPTL4 is a secreted protein, ANGPTL4 also controls lipoprotein metabolism and energy homeostasis as well as LPL-independent functions in the tissues where it is expressed. Targeting ANGPTL4 and other negative regulators of LPL (APOCIII and ANGPTL3) are novel therapeutic targets for treating dyslipidemia and cardiovascular diseases.